(3GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg hGdUdGI Ydi CfHjGFg GYde CfG aQZfG ef GdcJGH GdChd , hGdKGfi , Yf PcQ Ld GdYde GdfXQi hGdCOhjI GdeaQOI , hMGhdfG Cf fTQM ai gPG GdcJGH GdKGdK hfQcR ajgG GdLRA GdYedi GdLGeY ddUMI s
(3BNQgG (B:s
(3hefgG eG jNaa hjfai GdUOjO GdQOF , hefgG eG jUdM GdeRGL GdQOF , hefgG COhjI JVGO GdYahfg , hCcKQgG CaGhjg YWhjI s
(3fSNI NGeSI JTJed Ydi GdcJGH GdKGdKs
(3hgh GdNGU HGdCeQGV GdLRFjI GdhGbYI HCYVGA GdEfSGf YVhkGs
(3ef GdeaQb Edi GdbOes
(3XGgQgG hHGWfgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdWHs